Kajian Yuridis Penerapan Asas Keberlangsungan Usaha Dalam Penundaan Kewajiban Pembayaran Utang Untuk Mencegah Pailit (Jurnal Restorative Justice, 2023)
This research discusses the application of the Principle of Business Continuity in Debt Payment Suspension in Indonesia over the last three years. The Principle of Business Continuity is a bankruptcy law principle that allows companies to address financial difficulties through restructuring rather than bankruptcy. This study analyzes the Principle of Business Continuity in the context of Debt Payment Suspension and the influencing factors, including financial conditions, future prospects, restructuring plans, creditor support, and management. Practical recommendations include enhancing transparency, consulting legal and financial experts, and maintaining effective communication with creditors. The research also highlights the role of research in applying the Principle of Business Continuity in Debt Payment Suspension. It is expected that this research will provide guidance for companies, the government, creditors, and relevant parties in addressing financial and legal challenges with the aim of preserving business continuity and fairness in Debt Payment Suspension.